Terminology and Terminological Systems - Elkin, Peter L. (Health Informatics, 2012)
Twenty-five years ago the notion that terminology should be concept-based was all but unknown in healthcare; now almost all important terminologies are at least partly concept-based.  With no general model of what a terminology was or should be, there were no tools to support terminology development and maintenance.  Steady progress since then has improved both terminology content and the technology and processes used to sustain that content.  For students, practitioners and managers, terminology and its understanding will be an asset to be leveraged in care and research. As the first book devoted to the story of terminology in healthcare, Terminology and Terminological Systems emphasizes the central topics of terminology, such as inter-enterprise clinical and research data aggregation,  and will become vital to the professional lives of students of informatics. For students, practitioners and managers, terminology and its understanding will be an asset to be leveraged in care and research. As the first book devoted to the story of terminology in healthcare, Terminology and Terminological Systems emphasizes the central topics of terminology, such as inter-enterprise clinical and research data aggregation,  and will become vital to the professional lives of students of informatics.